Rectal Foreign Body in a 30 Year Old Male- A Case Report (Journal of Shaheed Suhrawardy Medical College, 2018)
Though anorectal foreign body cases are rare, they have become increasingly frequent in recent years. Although entrapped foreign bodies are most often related to sexual behavior, they can also result from ingestion or sexual assault. The diagnosis may be made by rectal examination and metallic objects can be confirmed by plain abdominal radiographs. Transanal removal is only possible for very low-lying objects, while patients with high-lying foreign bodies usually require an operative intervention. An early decision of laparotomy should only be made after subjecting the patient to suitable investigations to determine exact location of the object, in order to avoid any inadvertent damage to the adjoining vasculature as well as anal incontinence. . We report the case of a young male who presented at surgery department of Shaheed Suhrawardy medical college hospital with severe rectal pain due to insertion of an apple into rectum by some eunuchs. It was successfully removed transanally under spinal anesthesia. Post operative period was uneventful and referred for psychiatric consultation.J Shaheed Suhrawardy Med Coll, June 2017, Vol.9(1); 35-37